Answer:
Given f(x) and g(x), please find (fog)(X) and (gof)(x) f(x) = 2x g(x) = x+3
Given f(x) and g(x), please find (fog)(X) and (gof)(x)
f(x) = 2x g(x) = x+3
print Print document PDF list Cite
Quick Answer
(fog)(x) = 2x + 6
(gof)(x) = 2x + 3
Expert Answers
HALA718 eNotes educator| CERTIFIED EDUCATOR
f(x) = 2x
g(x) = x + 3
First let us find (fog)(x)
(fog)(x) = f(g(x)
= f(x+3)
= 2(x+3)
= 2x + 6
==> (fog)(x) = 2x + 6
Now let us find (gof)(x):
(gof)(x) = g(f(x)
= g(2x)
= 2x + 3
==> (gof)(x) = 2x + 3
Step-by-step explanation:
Answer:
A 28 because 7 times four
Step-by-step explanation:
Jacob must now invest $10,712,72 to have $50,000 for the party.
60v = $15
60v/60 = $15/60
v = 0.25
The original value of the baseball card is $0.25